2015
DOI: 10.1021/acs.jpcb.5b09196
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Aqueous Solutions of Dimethyl Sulfoxide by Spectroscopy in the Mid- and Near-Infrared: Experiments and Car–Parrinello Simulations

Abstract: The infrared and near-infrared spectra of the aqueous solutions of dimethyl sulfoxide are revisited. Experimental and computational vibrational spectra are analyzed and compared. The latter are determined as the Fourier transformation of the velocity autocorrelation function of data obtained from Car-Parrinello molecular dynamics simulations. The experimental absorption spectra are deconvolved, and the excess spectra are determined. The two-dimensional excess contour plot provides a means of visualizing and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
117
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 53 publications
11
117
0
Order By: Relevance
“…Again, the third PC has an extremum around x DMSO =0.5 indicating that it corresponds to 1:1 water‐DMSO dimers. This is in concert with the existing literature, in which experimental and theoretical studies confirmed that hydrogen‐bonded dimers are the predominant interspecies configuration …”
Section: Figuresupporting
confidence: 90%
See 2 more Smart Citations
“…Again, the third PC has an extremum around x DMSO =0.5 indicating that it corresponds to 1:1 water‐DMSO dimers. This is in concert with the existing literature, in which experimental and theoretical studies confirmed that hydrogen‐bonded dimers are the predominant interspecies configuration …”
Section: Figuresupporting
confidence: 90%
“…16 scans were averaged to obtain an appropriate signal‐to‐noise ratio. For further details on the data acquisition and treatment, for example, how the excess spectra were obtained, see the references …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The broad and strong hydroxyl (OH) stretching band of water dominates the high wavenumber region, i.e., 2800 to 3800 cm −1 . This band is commonly deconvolved into several sub-bands, indicating the different hydrogen-bonding states of water molecules [29,30]: The lower the wavenumber, the stronger the hydrogen bonding [31]. However, even with the naked eye, systematic differences between the three cases can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…[14] These uniquea ttributes of DMSO/waterm ixtures have motivated ag ood number of investigations on them. [12,15,16] Various experimental techniques have been employed to address these aqueousD MSO systems, such as dielectric relaxation spectroscopy, [17,18] vibrational spectroscopy, [19][20][21][22] neutron diffraction, [23] fluorescences pectroscopy, [24] molecular dynamics simulations, [25][26][27][28] etc. Al arge majority of these studies suggest that DMSO significantly impacts the donor/acceptor balance in water by participation of its oxygen lone pairs for accepting two hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%